2013
DOI: 10.1177/0961203313478302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tetra-arsenic tetra-sulfide on BXSB lupus-prone mice: a pilot study

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease of uncertain etiology that affects multiple tissues and organs. Arsenic trioxide (ATO) has been used in lupus-prone mice with a regulatory effect on immune abnormality. Tetra-arsenic tetra-sulfide (As4S4), a traditional Chinese medicine, is effective on acute promyelocytic leukemia with mild side effects than ATO. In this study, a pilot study was performed to investigate the effects and the mechanism of As4S4 on the lupus-prone BXSB mice. Improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…These results are consistent with our prior study on BXSB mice (Zhao et al, 2013)), and further demonstrate the effect of As 4 S 4 on inhibiting the disease of lupus-prone mice. Realgar, a mined ore, containing about 90% As 4 S 4, was employed to treat a variety of diseases, including syphilis, malignancy, malaria, and Lu reported that oral high-purity As 4 S 4 can be safely used for induction or long-term treatment in most patients with APL (Lu et al, 2001), which engaged our attention to investigate the effect of As 4 S 4 on lupus.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These results are consistent with our prior study on BXSB mice (Zhao et al, 2013)), and further demonstrate the effect of As 4 S 4 on inhibiting the disease of lupus-prone mice. Realgar, a mined ore, containing about 90% As 4 S 4, was employed to treat a variety of diseases, including syphilis, malignancy, malaria, and Lu reported that oral high-purity As 4 S 4 can be safely used for induction or long-term treatment in most patients with APL (Lu et al, 2001), which engaged our attention to investigate the effect of As 4 S 4 on lupus.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, it presented protective effect on liver and kidney with no obvious toxicity. These results are consistent with our prior study on BXSB mice (Zhao et al, )), and further demonstrate the effect of As 4 S 4 on inhibiting the disease of lupus‐prone mice.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations